RESHAPING OF CONOID TOOTH WITH COMPOSITE RESIN USING A SIMPLIFIED APPLICATION TECHNIQUE - Marcelo Figueiredo Lobato; Cristian Sbardelotto; Stephano Zerlottini Isaac; Leandro Augusto Hilger (Portal de Periódicos da Marinha do Brasil, 2019)
A beautiful smile is often considered to have an important role on people's lives, since it contributes to self-confidence and social relationships. Therefore, dental discrepancies such as conoid teeth could affect negatively one's life and, as long as the patient desires, intervention should take place. Conoid teeth have significant alterations of basic anatomy, size and shape, which lead to a non-proportional smile. This case report regards to a reshape of a conoid lateral incisor, using direct composites, in order to help the orthodontic work. The chosen technique to provide this reshape was developed by the Styleitaliano® group, in order to simplify the restorative steps, using only three composite shades (one for dentin, one for enamel and one for optical effect). This case report emphasizes that different dentistry areas, such as Cosmetic Dentistry and Orthodontics must perform together in order to achieve good results, especially in cases that require shape changes.